Tea and flavonoid intake predict osteoporotic fracture risk in elderly Australian women: A prospective study - Myers, G.; Prince, R.; Kerr, Deborah; Devine, A.; Woodman, R.; Lewis, J.; Hodgson, J. (American Society for Nutrition, 2015)
Background: Observational studies have linked tea drinking, a major source of dietary flavonoids, with higher bone density. However, there is a paucity of prospective studies examining the association of tea drinking and flavonoid intake with fracture risk. Objective: The objective of this study was to examine the associations of black tea drinking and flavonoid intake with fracture risk in a prospective cohort of women aged .75 y. Design: A total of 1188 women were assessed for habitual dietary intake with a food-frequency and beverage questionnaire. Incidence of osteoporotic fracture requiring hospitalization was determined through the Western Australian Hospital Morbidity Data system. Multivariable adjusted Cox regression was used to examine the HRs for incident fracture. Results: Over 10 y of follow-up, osteoporotic fractures were identified in 288 (24.2%) women; 212 (17.8%) were identified as a major osteoporotic fracture, and of these, 129 (10.9%) were a hip fracture. In comparison with the lowest tea intake category (=1 cup/wk), consumption of $3 cups/d was associated with a 30% decrease in the risk of any osteoporotic fracture (HR: 0.70; 95% CI: 0.50, 0.96). Compared with women in the lowest tertile of total flavonoid intake (from tea and diet), women in the highest tertile had a lower risk of any osteoporotic fracture (HR: 0.65; 95% CI: 0.47, 0.88), major osteoporotic fracture (HR: 0.66; 95% CI: 0.45, 0.95), and hip fracture (HR: 0.58; 95% CI: 0.36, 0.95). For specific classes of flavonoids, statistically significant reductions in fracture risk were observed for higher intake of flavonols for any osteoporotic fracture and major osteoporotic fracture, as well as flavones for hip fracture (P , 0.05). Conclusion: Higher intake of black tea and particular classes of flavonoids were associated with lower risk of fracture-related hospitalizations in elderly women at high risk of fracture.